Financial management behaviour among Malaysian smes owners in Kuala Selangor: some new insights from a qualitative study - Sa’ad, Shukriah; Mat Dangi, Mohamad Ridhuan; Ismail, Aida Hazlin; Zainal Abidin, Adnan (2025)
One of the critical elements for SMEs to continue improving their performance with a dynamic market in Malaysia is to practice prudent financial management. Therefore, this study aims to identify the owners' and firm characteristics and financial management practices among the SMEs owners in Kuala Selangor. The data was collected through an interview, and the results indicate the importance of ensuring all the available business resources are used efficiently and effectively to provide an optimum return. Findings from this study may be helpful to the Government and financial providers know the importance of educating the financial management knowledge among SMEs owners and understand the appropriate financial management tools adoption by SMEs owner in the sub-urban area in Selangor.